Coordination in multi-agent systems - Chen, Gang (2008)
Coordination, as an art of managing interdependencies among activities, is one of the central research issues in multi-agent systems. This thesis addresses agent coordination in task-oriented domains where multiple agents cooperating with each other in order to achieve a series of tasks.